2022
DOI: 10.1111/jfbc.14419
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Ginkgo biloba in treating type 2 diabetes mellitus combined with non‐alcoholic fatty liver disease based on network pharmacology, molecular docking, and experimental evaluations

Abstract: Ginkgo biloba has gained increasing attention owing to its remarkable effects against cardiovascular disease. However, the role of G. biloba in hepatic lipid metabolism disorders in type 2 diabetes mellitus (T2DM) combined with non‐alcoholic fatty liver disease (NAFLD) and its underlying mechanisms have not been elucidated. Here, the effective ingredients and mechanisms of action of G. biloba in T2DM combined with NAFLD were investigated via an integrated strategy of network pharmacology and molecular docking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…By decreasing the transcription of pro-apoptotic caspase-9 and JNK and increasing the activity of anti-apoptotic Bcl-2 protein, Ginkgo biloba extract EGb761 attenuated proinflammatory and pro-apoptotic processes, thus preventing the initiation of apoptotic signaling cascade and thus protecting the integrity of the mitochondrial membrane (35). Research has demonstrated that the administration of Ginkgo biloba extract can impede adipogenesis and modulate lipid metabolism, resulting in a decrease in body weight and food consumption (8). Diabetic peripheral vasculopathy had a prevalence of about 20% in diabetic patients and was a common vascular complication of T2DM, with the lower limb arteries being the main site of onset (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By decreasing the transcription of pro-apoptotic caspase-9 and JNK and increasing the activity of anti-apoptotic Bcl-2 protein, Ginkgo biloba extract EGb761 attenuated proinflammatory and pro-apoptotic processes, thus preventing the initiation of apoptotic signaling cascade and thus protecting the integrity of the mitochondrial membrane (35). Research has demonstrated that the administration of Ginkgo biloba extract can impede adipogenesis and modulate lipid metabolism, resulting in a decrease in body weight and food consumption (8). Diabetic peripheral vasculopathy had a prevalence of about 20% in diabetic patients and was a common vascular complication of T2DM, with the lower limb arteries being the main site of onset (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…A serious concern for healthcare was diabetes mellitus (DM), which has several features including chronic hyperglycemia and aberrant protein, fat, and carbohydrate metabolism (2,(4)(5)(6). Diabetes is one of the five priority noncommunicable diseases (NCDs) in WHO's NCDs control strategy (7,8). Ongoing complex, expensive efforts are required to prevent and treat chronic problems in patients with diabetes, especially type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, docking of receptor proteins with dendrobine was performed using AutoDock Vina [ 20 ]. According to references [ 21 23 ], a binding energy of ≤ -5 kJ/mol is commonly considered the standard for successful docking. Under this criterion, if the docking binding energy is ≤ -7 kJ/mol, it can be considered that the molecule and its target exhibit a high level of interaction stability, indicating a potentially effective binding between them.…”
Section: Methodsmentioning
confidence: 99%
“…Persistent hyperglycemia is known to elevate oxidative stress and induced IR in target tissues, thereby playing a significant role in the development of T2DM. Furthermore, impaired mitochondrial function caused by IR can lead to reducing insulin sensitivity and elevating blood glucose levels in a vicious cycle [ 4 ].…”
Section: Introductionmentioning
confidence: 99%